The Relationship between Parental Characteristics and Social Interaction Skills of Autistic Children in SLB Sragen Region - Fitri, Idha Rosydiana; Arifah , Siti (Journal La Medihealtico, 2023)
Autism is a disorder that occurs in brain tissue where the condition is a developmental disorder characterized by the inability to carry out social interactions, inability to communicate and repetitive behavior. This causes an autistic child to prefer to be alone and unable to communicate with other people well. Parental involvement in parenting significantly increases the developmental progress of children with autism, including allocating time for joint activities, frequent interaction, financial assistance, active parenting, and being involved in playing with children. Thus, the role of parents is very much needed. to provide care in the development of autistic children. This research aims to determine the relationship between parental characteristics and social interaction abilities for Autistic Children in SLB in the Sargen area. This research used a cross sectional method involving 60 parents who had autistic children at the Sragen Regency Special School which was conducted in September 2023. Social interaction data was measured using ATEC (Autism Treatment Evaluation Checklist). The data analysis used is the data normality test and continued with the Chisquare test to determine the relationship between variables. There is a weak relationship between age, parental education, employment and family income with the social interaction abilities of autistic children in the Sragen Regional Special School. (p 0.04 phi = 0.34, p 0.015 phi 0.282, p 0.007 phi -0.268, p 0.01 phi 0.336). Several parental characteristics have a relationship with the social interaction abilities of autistic children, although the categories are weak.